Schottky junction type beta nuclear battery based on porous SiC and preparation method of Schottky junction type beta nuclear battery

By using porous SiC materials and graphene to form a three-dimensional Schottky junction-radiated volt nuclear battery in Schottky junction, the problems of small radiation area and low energy conversion efficiency in the prior art are solved, and more efficient energy conversion and Simpler craftsmanship.

CN119495462APending Publication Date: 2025-02-21NUCLEAR POWER INSTITUTE OF CHINA
0 Cites 0 Cited by

Patent Information

Application Number
CN202410663574.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-02-21

Smart Images

  • Figure HDA0004860443660000011
    Figure HDA0004860443660000011
  • Figure HDA0004860443660000012
    Figure HDA0004860443660000012
  • Figure HDA0004860443660000021
    Figure HDA0004860443660000021
Patent Text Reader

Abstract

The invention discloses a Schottky junction type beta nuclear battery based on porous SiC and a preparation method of the Schottky junction type beta nuclear battery, and belongs to the technical field of nuclear batteries. The Schottky junction type beta nuclear battery comprises a lower electrode, a highly-doped n-type SiC substrate layer, a lowly-doped n-type SiC epitaxial layer and a graphene upper electrode which are sequentially arranged, a porous nano structure is etched on the surface of the highly-doped n-type SiC substrate layer, and a Schottky junction is of a three-dimensional structure; the Schottky junction type beta nuclear battery has the advantages of being large in radiation area, small in incident particle energy loss, easy to manufacture and high in energy conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nuclear batteries, and in particular to a Schottky junction β nuclear battery based on porous SiC and a preparation method thereof. Background Art

[0002] The working principle of the β-type voltaic effect isotope battery is to use the electrons released by the decay of the β-isotope source to act on the semiconductor material. The generated electron-hole pairs form a current under the action of the built-in electric field, thereby converting the decay energy into electrical energy. Therefore, the location where the β-rays reach the material and the collection of the generated electron-hole pairs are crucial, so the selection of the transducer material and the structural design of the device have become the key to the design. Silicon carbide (SiC) is the third-generation wide bandgap semiconductor material with the most mature commercial development. It has the advantages of large bandgap width, strong thermal stability, high thermal conductivity, stable chemical properties, good electron transport performance, and strong radiation resistance. At the same time, the doping process of p-type or n-type SiC materials is mature, and they are compatible with silicon semiconductor planar processes. Therefore, it is widely used in β-radiation voltaic effect nuclear batteries.

[0003] For pn junction or pin junction SiC nuclear batteries, ohmic contacts need to be made on both sides of the pn junction or pin junction. However, it is difficult to make ohmic contacts on P-type SiC, which requires ion implantation and high-temperature annealing, resulting in complex processes and high manufacturing costs for pn junction or pin junction nuclear batteries. Compared with pn junction, the selection of Schottky device materials is easier, so it is more convenient to solve problems such as barrier height, carrier diffusion distance, and radiation damage resistance. In addition, the carriers in Schottky devices have a longer recombination life than junctions, so the use of Schottky devices can achieve higher conversion efficiency.

[0004] The metal layer in the common Schottky radiovoltaic nuclear battery mostly uses a single or multi-layer mixed metal thin film electrode to reduce the blocking effect on the decay particles of the radioactive source. However, the current method not only increases the difficulty and complexity of the process, but also the conductivity of the thin layer of metal is not particularly ideal, which affects the transmission and collection of electron-hole pairs, making the efficiency of the Schottky junction radiovoltaic nuclear battery low. On the other hand, the utilization efficiency of semiconductor materials for radiation sources is mainly determined by their specific surface area. Conventional isotope batteries use a planar structure, which has a simple preparation process and is easy to integrate, but the absorption efficiency of the radiation source is low. Summary of the invention

[0005] The present invention aims to solve the technical problems of the existing Schottky junction radiovoltaic nuclear battery, such as small radiation area, large incident particle energy loss and low energy conversion efficiency. The present invention aims to provide a Schottky junction β nuclear battery based on porous SiC and a preparation method thereof, which has the characteristics of large radiation area, small incident particle energy loss, simple preparation and high energy conversion efficiency.

[0006] The present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a Schottky junction β-core battery based on porous SiC, comprising a lower electrode, a highly doped n-type SiC substrate layer, a low doped n-type SiC epitaxial layer, and a graphene upper electrode arranged in sequence, wherein the surface of the highly doped n-type SiC substrate layer is etched with a porous nanostructure, and the Schottky junction is a three-dimensional structure.

[0008] As a further technical solution of the present invention, the doping concentration of the highly doped n-type SiC substrate layer is 1×10 18 ~5×10 18 cm -3 , thickness is 350um.

[0009] As a further technical solution of the present invention, the doping concentration of the low-doped n-type SiC epitaxial layer is 6×10 13 ~4×10 15 cm -3 , thickness is 10~15um.

[0010] As a further technical solution of the present invention, the lower electrode is Ni and has a thickness of 100 to 300 nm.

[0011] As a further technical solution of the present invention, the thickness of the graphene upper electrode is 250 to 500 nm.

[0012] Another object of the present invention is to provide a method for preparing a Schottky junction β-core battery based on porous SiC, comprising the following steps:

[0013] S1. Cut the highly doped n-type SiC circular single crystal into the required size and shape, and remove surface impurities and oxides;

[0014] S2, preparing SiC porous nanostructures by electrochemical etching;

[0015] S3, uniformly growing a low-doped n-type SiC epitaxial layer on the etched SiC porous nanostructure by PECVD technology;

[0016] S4, preparing the lower electrode by magnetron sputtering method;

[0017] S5. Evenly drop the graphene oxide dispersion onto the SiC epitaxial wafer obtained in S3, and then place the epitaxial wafer in an atmosphere of hydrazine hydrate vapor so that the graphene oxide layer on the epitaxial wafer is gradually reduced to graphene by the hydrazine hydrate vapor, thereby forming a SiC-graphene Schottky junction, and the graphene also serves as an upper electrode.

[0018] As a further technical solution of the present invention, in S1, removing surface impurities and oxides specifically includes:

[0019] The cut wafers were ultrasonically cleaned with acetone, anhydrous ethanol and distilled water for 15 min to remove surface impurities, and then immersed in a mixture of hydrofluoric acid: anhydrous ethanol = 1:1 for 2 min to remove surface oxides.

[0020] As a further technical solution of the present invention, in S2, preparing SiC porous nanostructure by electrochemical etching specifically includes:

[0021] The highly doped n-type SiC circular single crystal crystal cleaned by S1 was used as the anode and the graphite sheet as the cathode. The distance between the anode and cathode was 20 cm. Hydrofluoric acid, ethanol and hydrogen peroxide were mixed into an electrolyte in a volume ratio of (3-8):6:1. The etching cycle number was 600-670 times, the pulse voltage was 15-20 V, and the period of the pulse voltage was 0.8 s.

[0022] As a further technical solution of the present invention, a DC voltage is applied for 30 seconds after etching is completed.

[0023] As a further technical solution of the present invention, in S4, the sputtering time is 0.5h.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] 1. In the Schottky junction β-core battery structure of the present invention, graphene and SiC form a three-dimensional Schottky junction, and the inner wall of the nano-channel of SiC forms a Schottky junction structure with the graphene layer, which greatly increases the effective radiation area, thereby improving the current density.

[0026] 2. In the Schottky junction β-core battery structure of the present invention, graphene is used as the upper electrode, so that the incident particles can avoid the loss of passing through the ordinary Schottky metal layer and directly enter the depletion region, further improving the energy conversion efficiency of the β-core battery.

[0027] 3. In the Schottky junction β-nuclear battery structure of the present invention, graphene with only atomic layer thickness and excellent conductivity is brought into contact with semiconductor silicon material to form a Schottky junction, which not only effectively reduces the blocking effect of the metal layer on the incident particles, but also improves the transmission and collection capacity of electron-hole pairs, and can further reduce the unit volume of the battery, providing guidance for the development of miniature radiovoltaic isotope batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0029] Figure 1 It is a structural schematic diagram of the present invention;

[0030] Figure 2 The current-voltage curve of the device prepared in Example 2 in a passive state;

[0031] Figure 3 This is the current-voltage curve of the device prepared in Example 2 under 17keV, 10mCi irradiation;

[0032] Figure 4 This is the current-time curve of the device prepared in Example 2 under 17keV, 10mCi irradiation;

[0033] Figure 5 This is the voltage-time curve of the device prepared in Example 2 under 17 keV, 10 mCi irradiation.

[0034] Marks and corresponding parts names in the attached drawings:

[0035] 1-highly doped n-type SiC substrate layer, 2-porous nanostructure, 3-lowly doped n-type SiC epitaxial layer, 4-graphene upper electrode, 5-lower electrode. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0037] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details are not necessarily employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known structures, circuits, materials, or methods are not specifically described.

[0038] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or sub-combination. In addition, it will be appreciated by those of ordinary skill in the art that the figures provided herein are for illustrative purposes and that the figures are not necessarily drawn to scale. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0039] In the description of the present invention, the directions or positional relationships indicated by terms such as “front”, “rear”, “left”, “right”, “up”, “down”, “vertical”, “horizontal”, “high”, “low”, “inside” and “outside” are based on the directions or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limiting the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment provides a Schottky junction β-core battery based on porous SiC, such as Figure 1 As shown, it includes a lower electrode 5, a highly doped n-type SiC substrate layer 1, a low doped n-type SiC epitaxial layer 3, and a graphene upper electrode 4 arranged in sequence from bottom to top. The surface of the highly doped n-type SiC substrate layer 1 is etched with a porous nanostructure 2, and the Schottky junction is a three-dimensional structure.

[0042] In the Schottky junction type beta-nuclear battery structure of the present invention, graphene and SiC form a three-dimensional Schottky junction, and the inner wall of the nano-channel of SiC forms a Schottky junction structure with the graphene layer, which greatly increases the effective radiation area, thereby improving the current density; the graphene is also used as an upper electrode, so that the incident particles can avoid the loss of passing through the ordinary Schottky metal layer and directly enter the depletion region, further improving the energy conversion efficiency of the beta-nuclear battery; the graphene with only atomic layer thickness and excellent conductivity is contacted with the semiconductor silicon material to form a Schottky junction, which not only effectively reduces the blocking effect of the metal layer on the incident particles, but also improves the transmission and collection capacity of electron-hole pairs, and can further reduce the unit volume of the battery, providing guidance for the development of miniature radiovoltaic isotope batteries.

[0043] Example 2

[0044] This embodiment provides a method for preparing a Schottky junction β-core battery based on porous SiC, comprising the following steps:

[0045] (1) First, a 4-inch highly doped n-type 4H-SiC circular single crystal was cut into 0.5×1.5 cm 2 (length × width) of a small chip.

[0046] (2) The small chip was ultrasonically cleaned with acetone, anhydrous ethanol and distilled water for 15 minutes to remove surface impurities, and then immersed in a mixture of hydrofluoric acid (30%): anhydrous ethanol (99.7%) = 1:1 for 2 minutes to remove surface oxides.

[0047] (3) The cleaned highly doped n-type SiC circular single crystal was used as the anode and the graphite sheet as the cathode. The distance between the anode and cathode was 20 cm. Hydrofluoric acid, ethanol and hydrogen peroxide were mixed into an electrolyte in a volume ratio of 3:6:1. The etching cycle was 622 times, the pulse voltage was 17 V, and the period of the pulse voltage was 0.8 s, where T on =0.4s, T off =0.4s, and after etching is completed, a DC voltage is applied for 30s, in order to completely peel off the SiC porous nanostructure from the substrate and ensure that the morphology and film structure are not destroyed.

[0048] (4) A low-doped n-type SiC layer with a thickness of 10 μm and a doping concentration of 6×10 13 cm -3 .

[0049] (5) The back of the SiC epitaxial wafer was encapsulated with tape as a mask to construct a sputtering area. Ni was sputtered by magnetron sputtering to prepare an ohmic contact back electrode. The sputtering time was 0.5 h and the Ni layer thickness was 150 nm.

[0050] (6) The graphene oxide dispersion is evenly dropped onto the SiC epitaxial wafer (the epitaxial wafer is protected by tape on all sides), and then the epitaxial wafer is placed in a glass watch glass with 0.8 ml of hydrazine hydrate solution added, the watch glass is sealed with tape, and the watch glass is heated at 90°C so that the graphene oxide layer on the epitaxial wafer is gradually reduced to graphene by hydrazine hydrate vapor, thereby forming a SiC-graphene Schottky junction, and the graphene also serves as the upper electrode.

[0051] (7) The upper and lower electrodes are led out with copper wires, and silver paste is applied on a glass sheet cut into a size of 2 cm × 2 cm. The port of the lower electrode is then peeled open and the silver paste is pressed into the lower electrode. The silver paste is then used to fix the lower electrode. The back of the silicon carbide with 150 nm thick Ni sputtered on the back is then pressed onto the silver paste. At this time, the lower electrode is fixed on the glass plate. The silver paste is then applied to the upper electrode portion of the SiC sheet. The wire is fixed with the silver paste and then dried at 100°C for 2 hours to complete the curing of the silver paste and prepare the device.

[0052] The device prepared in this embodiment was tested for performance, and the results are as follows: Figure 2 to Figure 5 As shown, from Figure 2 to Figure 5 It can be seen that the Schottky junction SiC transducer device prepared in this embodiment is 17keV and the beam current is 10mCi / cm 2 In this case, the short-circuit current is 24.10nA, the open-circuit voltage is 1.09V, and the conversion efficiency reaches 2.2%.

[0053] Example 3

[0054] This embodiment provides a method for preparing a Schottky junction β-core battery based on porous SiC, comprising the following steps:

[0055] (1) First, a 4-inch highly doped n-type 4H-SiC circular single crystal was cut into 0.5×1.5 cm 2 (length × width) of a small chip.

[0056] (2) The small chip was ultrasonically cleaned with acetone, anhydrous ethanol and distilled water for 15 minutes to remove surface impurities, and then immersed in a mixture of hydrofluoric acid (30%): anhydrous ethanol (99.7%) = 1:1 for 2 minutes to remove surface oxides.

[0057] (3) The cleaned highly doped n-type SiC circular single crystal was used as the anode and the graphite sheet as the cathode. The distance between the anode and cathode was 20 cm. Hydrofluoric acid, ethanol and hydrogen peroxide were mixed into an electrolyte in a volume ratio of 6:6:1. The etching cycle was 645 times, the pulse voltage was 17 V, and the period of the pulse voltage was 0.8 s, where T on =0.4s, T off =0.4s, and after etching is completed, a DC voltage is applied for 30s, in order to completely peel off the SiC porous nanostructure from the substrate and ensure that the morphology and film structure are not destroyed.

[0058] (4) A low-doped n-type SiC layer with a thickness of 10 μm and a doping concentration of 6×10 13 cm -3 .

[0059] (5) The back of the SiC epitaxial wafer was encapsulated with tape as a mask to construct a sputtering area. Ni was sputtered by magnetron sputtering to prepare an ohmic contact back electrode. The sputtering time was 0.5 h and the Ni layer thickness was 150 nm.

[0060] (6) The graphene oxide dispersion is evenly dropped onto the SiC epitaxial wafer (the epitaxial wafer is protected by tape on all sides), and then the epitaxial wafer is placed in a glass watch glass with 0.8 ml of hydrazine hydrate solution added, the watch glass is sealed with tape, and the watch glass is heated at 90°C so that the graphene oxide layer on the epitaxial wafer is gradually reduced to graphene by hydrazine hydrate vapor, thereby forming a SiC-graphene Schottky junction, and the graphene also serves as the upper electrode.

[0061] (7) The upper and lower electrodes are led out with copper wires, and silver paste is applied on a glass sheet cut into a size of 2 cm × 2 cm. The port of the lower electrode is then peeled open and the silver paste is pressed into the lower electrode. The silver paste is then used to fix the lower electrode. The back of the silicon carbide with 150 nm thick Ni sputtered on the back is then pressed onto the silver paste. At this time, the lower electrode is fixed on the glass plate. The silver paste is then applied to the upper electrode portion of the SiC sheet. The wire is fixed with the silver paste and then dried at 100°C for 2 hours to complete the curing of the silver paste and prepare the device.

[0062] Example 4

[0063] This embodiment provides a method for preparing a Schottky junction β-core battery based on porous SiC, comprising the following steps:

[0064] (1) First, a 4-inch highly doped n-type 4H-SiC circular single crystal was cut into 0.5×1.5 cm 2 (length × width) of a small chip.

[0065] (2) The small chip was ultrasonically cleaned with acetone, anhydrous ethanol and distilled water for 15 minutes to remove surface impurities, and then immersed in a mixture of hydrofluoric acid (30%): anhydrous ethanol (99.7%) = 1:1 for 2 minutes to remove surface oxides.

[0066] (3) The cleaned highly doped n-type SiC circular single crystal was used as the anode and the graphite sheet as the cathode. The distance between the anode and cathode was 20 cm. Hydrofluoric acid, ethanol and hydrogen peroxide were mixed into an electrolyte in a volume ratio of 8:6:1. The etching cycle was 660 times, the pulse voltage was 17 V, and the period of the pulse voltage was 0.8 s, where T on =0.4s, T off =0.4s, and after etching is completed, a DC voltage is applied for 30s, in order to completely peel off the SiC porous nanostructure from the substrate and ensure that the morphology and film structure are not destroyed.

[0067] (4) A low-doped n-type SiC layer with a thickness of 10 μm and a doping concentration of 6×10 13 cm -3 .

[0068] (5) The back of the SiC epitaxial wafer was encapsulated with tape as a mask to construct a sputtering area. Ni was sputtered by magnetron sputtering to prepare an ohmic contact back electrode. The sputtering time was 0.5 h and the Ni layer thickness was 150 nm.

[0069] (6) The graphene oxide dispersion is evenly dropped onto the SiC epitaxial wafer (the epitaxial wafer is protected by tape on all sides), and then the epitaxial wafer is placed in a glass watch glass with 0.8 ml of hydrazine hydrate solution added, the watch glass is sealed with tape, and the watch glass is heated at 90°C so that the graphene oxide layer on the epitaxial wafer is gradually reduced to graphene by hydrazine hydrate vapor, thereby forming a SiC-graphene Schottky junction, and the graphene also serves as the upper electrode.

[0070] (7) The upper and lower electrodes are led out with copper wires, and silver paste is applied on a glass sheet cut into a size of 2 cm × 2 cm. The port of the lower electrode is then peeled open and the silver paste is pressed into the lower electrode. The silver paste is then used to fix the lower electrode. The back of the silicon carbide with 150 nm thick Ni sputtered on the back is then pressed onto the silver paste. At this time, the lower electrode is fixed on the glass plate. The silver paste is then applied to the upper electrode portion of the SiC sheet. The wire is fixed with the silver paste and then dried at 100°C for 2 hours to complete the curing of the silver paste and prepare the device.

[0071] Comparative Example

[0072] The difference between this comparative example and Example 2 is that step (3) is not performed, that is, planar SiC is used.

[0073] The device prepared in this comparative example was tested for performance, and the short-circuit current was 18.93 nA, the open-circuit voltage was 0.95 V, and the conversion efficiency was 1.5%.

[0074] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A Schottky junction β-core battery based on porous SiC, characterized in that: The invention comprises a lower electrode (5), a highly doped n-type SiC substrate layer (1), a low doped n-type SiC epitaxial layer (3), and a graphene upper electrode (4) which are arranged in sequence, wherein a porous nanostructure (2) is etched on the surface of the highly doped n-type SiC substrate layer (1), and the Schottky junction is a three-dimensional structure.

2. A Schottky junction β-core battery based on porous SiC according to claim 1, characterized in that: The doping concentration of the highly doped n-type SiC substrate layer (1) is 1×10 18 ~5×10 18 cm -3 , thickness is 350um.

3. A Schottky junction β-core battery based on porous SiC according to claim 1, characterized in that: The doping concentration of the low-doped n-type SiC epitaxial layer (3) is 6×10 13 ~4×10 15 cm -3 , thickness is 10~15um.

4. A Schottky junction β-core battery based on porous SiC according to claim 1, characterized in that: The lower electrode (5) is Ni, and has a thickness of 100-300 nm.

5. The Schottky junction β-core battery based on porous SiC according to claim 1, characterized in that: The graphene upper electrode (4) has a thickness of 250 to 500 nm.

6. A method for preparing a Schottky junction β-core battery based on porous SiC, characterized in that: The following steps are involved: S1. Cut the highly doped n-type SiC circular single crystal into the required size and shape, and remove surface impurities and oxides; S2, preparing SiC porous nanostructures by electrochemical etching; S3, uniformly growing a low-doped n-type SiC epitaxial layer on the etched SiC porous nanostructure by PECVD technology; S4, preparing the lower electrode by magnetron sputtering method; S5. Evenly drop the graphene oxide dispersion onto the SiC epitaxial wafer obtained in S3, and then place the epitaxial wafer in an atmosphere of hydrazine hydrate vapor so that the graphene oxide layer on the epitaxial wafer is gradually reduced to graphene by the hydrazine hydrate vapor, thereby forming a SiC-graphene Schottky junction, and the graphene also serves as an upper electrode.

7. The method for preparing a Schottky junction β-core battery based on porous SiC according to claim 6, characterized in that: In S1, removing surface impurities and oxides specifically includes: The cut wafers were ultrasonically cleaned with acetone, anhydrous ethanol and distilled water for 15 min to remove surface impurities, and then immersed in a mixture of hydrofluoric acid: anhydrous ethanol = 1:1 for 2 min to remove surface oxides.

8. The method for preparing a Schottky junction β-core battery based on porous SiC according to claim 6, characterized in that: In S2, preparing SiC porous nanostructure by electrochemical etching specifically includes: The highly doped n-type SiC circular single crystal crystal cleaned by S1 was used as the anode and the graphite sheet as the cathode. The distance between the anode and cathode was 20 cm. Hydrofluoric acid, ethanol and hydrogen peroxide were mixed into an electrolyte in a volume ratio of (3-8):6:

1. The etching cycle number was 600-670 times, the pulse voltage was 15-20 V, and the period of the pulse voltage was 0.8 s.

9. The method for preparing a Schottky junction β-core battery based on porous SiC according to claim 8, characterized in that: After etching is completed, a DC voltage is applied for 30 seconds.

10. The method for preparing a Schottky junction β-core battery based on porous SiC according to claim 8, characterized in that: In S4, the sputtering time is 0.5 h.